AN ECONOMIC ANALYSIS OF THE FACTORS DETERMINING THE ROLE OF RURAL WOMEN IN AGRICULTURAL PRODUCTION IN BAGHDAD GOVERNORATE. - Abed, M. N.; Ahmad, A. F. Ahmad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The study aims to determine the impact of economic and social determinants on the size of women's contribution to agricultural work. The research used qualitative response models to determine the impact of the explanatory variables (age, marital status, educational level, training skills, experience in agricultural work, NGO support, health status, family size, experience in secondary agricultural work, use of agricultural machinery in plant production) and their impact on the variable affiliated with the participation of rural women for a random sample of (384) women in separate rural areas in Baghdad Governorate. The results of the analysis showed that the size of the family and the use of mechanization had a negative and weak effect on the contribution of women. As the increase in the size of the family leads to an increase in its household burdens at the expense of its work in farm work. And because the use of mechanization is limited to men, the increased use of technology, especially modern ones, works to reduce women's working hours on the farm. The rest of the variables had a positive and significant impact on their contribution. Accordingly, the research recommends the provision of health and educational services for women, as well as their involvement in training, extension, and economic and financial empowerment programs to raise their contribution to achieving sustainable agricultural development.